CONTAGION EFFECT OF COVID-19 PANDEMIC ON FINANCIAL STOCK MARKET - Muhammad Reza Pahlevi; NGUYEN Than Liem; Faurani I Santi Singagerda (Prosiding International conference on Information Technology and Business (ICITB), 2020)
This study was able to investigate an interrelationship and the effect of each variable to the affecting variables of Covid-19 Pandemic on The Financial Market Index in The Indonesia Stock Exchange during the coronaviruses pandemic. Using daily Covid-19 was confirmed cases of the United States and China, and Stock Index of the United States, China, and Indonesia over the period from January 1, 2020, to October 30, 2020. The result of this study found that the stock Index responded to the interrelationship because of the Covid-19 pandemic and it was also the stock Index reaction to each other.Keywords   :Covid-19 Pandemic, Pandemic, Financial Market, Stock Index